Parametric investigation on an industrial electromagnetic continuous casting mould performance. Issue 4 (3rd February 2017) - Zhang, Lintao; Deng, Anyuan; Cameron, Ian; Wang, Engang; Sienz, Johann
Graphical abstract: Abstract: This research aimed at conducting a quantitative investigation of process parameters on the magnetic field contribution in an electromagnetic continuous casting mould. The Taguchi method (4 factors and 3 factor value levels: L9 orthogonal array) was adopted to design matrix of the simulation runs and the analysis of variance was used to evaluate the contributions of each control factor. The simulations were conducted based on the finite element method and the numerical set-up was validated by the designed experiment. The results showed that the applied alternating current magnitude contributed most (76.64%) to the magnetic field level in the mould, compared to the other control factors. It was followed by the slit length (17.72%), the alternating current frequency (4.17%) and the slit width (1.57%).